2001
DOI: 10.1016/s0167-4889(01)00107-0
|View full text |Cite
|
Sign up to set email alerts
|

NADH oxidase activity (NOX) and enlargement of HeLa cells oscillate with two different temperature-compensated period lengths of 22 and 24 minutes corresponding to different NOX forms

Abstract: NOX proteins are cell surface-associated and growth-related hydroquinone (NADH) oxidases with protein disulfide-thiol interchange activity. A defining characteristic of NOX proteins is that the two enzymatic activities alternate to generate a regular period length of about 24 min. HeLa cells exhibit at least two forms of NOX. One is tumor-associated (tNOX) and is inhibited by putative quinone site inhibitors (e.g., capsaicin or the antitumor sulfonylurea, LY181984). Another is constitutive (CNOX) and refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…[1]. The rate of enlargement of plant, animal and bacterial cells also oscillates with a period of 24 min [12][13][14]29,30]. The 24 min periodic behavior is exhibited by pure recombinant tNOX protein and is accompanied by a recurring pattern of amide I/amide II FTIR and CD spectral changes suggestive of a-helix-b-sheet transformations [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1]. The rate of enlargement of plant, animal and bacterial cells also oscillates with a period of 24 min [12][13][14]29,30]. The 24 min periodic behavior is exhibited by pure recombinant tNOX protein and is accompanied by a recurring pattern of amide I/amide II FTIR and CD spectral changes suggestive of a-helix-b-sheet transformations [31].…”
Section: Discussionmentioning
confidence: 99%
“…The alternation of activities imparts a time-keeping function to ECTO-NOX proteins. The length of the period is temperature independent [12][13][14] and entrainable [15][16][17][18], both features of the biological clock [19,20]. Site directed mutagensis (cysteine to alanine replacements) of the tNOX cDNA has generated recombinant tNOX forms with period lengths of less than and greater than 24 min [21].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative and interchange activities of the tNOX protein also alternate but generate a 22 min rather than a 24 min period (9). Inhibition by vanilloids such as capsaicin (3) and by antitumor sulfonylureas (10) distinguishes tNOX from other NADH oxidases.…”
mentioning
confidence: 99%
“…Although physiological roles of the redox system are not yet completely understood, functions in which plasma membrane redox systems have been implicated are proton extrusion and control of internal pH (25), generation of superoxide (26), reduction of ferric irons and iron uptake (27,28), control of cell growth and proliferation (5,29,30), and biological timekeeping (31,32). Comprehensive reviews of the plasma membrane redox system are found elsewhere (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%